Column chromatographic extraction for quickly separating the volatiles, flavonoids, and pectin from tangerine peel. Issue 3 (11th February 2016) - Chen, Diling; Huang, Yingran; Liang, Hualun; Xie, Yizhen
ABSTRACT: Tangerine peel, a very abundant natural resource, only part of which has been used in traditional Chinese medicine and health foods but most were discarded as the waste, which should be fully utilized. Previous studies showed its functional components include volatiles, ﬂavonoids, phenolic acids, and pectin, all of which cannot be effectively extracted through traditional methods. A column chromatographic extraction with gradient elution was developed for one-step extraction of all bioactive substances from tangerine peel. Dried material was loaded into a column eluted with 2-fold of petroleum ether: ethanol (7:3, PE) for the volatiles fraction. Sequentially eluted with 4-fold of ethanol: water (5:5, EW) then separated into ﬂavonoids and polysaccharides by 80% ethanol precipitation of polysaccharides. The third eluted with 5-fold of water and then 60% ethanol precipitation of pectin. Through these procedures, volatiles, ﬂavonoids, and pectin in tangerine peel were simultaneously extracted at 98% extraction rates and simply separated at higher than 95% recovery rates. To further reduce solvent consumption and the volume of the final extract, cyclic column chromatographic extraction should be used. The method provides a simple and high efﬁcient extraction and separation of a wide range bioactive substances.